Metastatic esophagogastric adenocarcinoma: trends in first-line treatment and predictive factors for the implementation of HER2 testing in clinical practice during the first year after trastuzumab market approval - Gencer, Deniz; Hofheinz, Ralf-Dieter (Journal of cancer research and clinical oncology, 2013)
PurposeLittle is known about the use of first-line chemotherapy in clinical practice in patients with advanced esophagogastric adenocarcinoma, and no data have been published regarding potential obstacles for the implementation of molecular testing for targeted agents in this patient group. Here, we sought to evaluate factors influencing treatment decisions with special focus on the implementation of HER2 testing during the first year after trastuzumab market approval in Germany.MethodsA total of 754 patients undergoing treatment decisions for palliative first-line therapy in 2010 were documented using Therapiemonitor®. Drug use and intensity of first-line treatment were analyzed. Data on HER2 testing and test algorithm are described, and variables influencing HER2 testing were selected using bivariate analysis. Significant factors were included in a multivariate logistic regression analysis.ResultsCompared with previous years, treatment intensity has further increased. The use of chemotherapy triplets rose from 10.1 % in 2006 to 60.3 % in 2010. In 2010, 49.1 % of patients were tested for HER2 and in 52.2 % of these patients the currently proposed test algorithm was used. Using multivariate logistic regression analysis age ≥67 years and “initiating institution: practice” were found to negatively impact the likelihood of HER2 testing, while treatment goal “prevention of progression”, multiple metastases and a Karnofsky status >80 % showed positive correlation with HER2 testing.ConclusionThe tendency to use more intensive first-line chemotherapy regimens in patients with advanced esophagogastric adenocarcinoma continued in 2010. Only a minority of patients had an access to the appropriate molecular diagnostics and therefore to treatment with trastuzumab. The access was limited due to the preselection following individual, clinical and institutional factors.
Published: 19 October 2012
Gesehen am 02.05.2018